PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI TAHUN PELAJARAN 2019/2020 - I Made Suwastika; Marsono (Guna Widya: Jurnal Pendidikan Hindu, 2020)
The purpose of this study was to study the implementation of the Two Stay Two Stray cooperative learning model in improving student learning outcomes in Hindu religion class VII in SMP Negeri 1 Melaya 2019/2020. This research is a classroom action research with cycle formation research procedures. Each cycle consists of four screens: planning, implementing actions, observing and reflecting. Data collection technique through observation and test. This data collection uses an instrument consisting of observation sheets of observations of students and teachers in the learning process, while to study the quality of student learning outcomes used an evaluation / test sheet. The results of the data analysis showed an increase in the average Hindu learning outcomes through the application of the Two Stay Two Stray cooperative model from the pre-cycle rack reaching a score of 62.9 in the first cycle reaching a score of 71.5 or up 8.6 points from the pre-cycle achieving a score of 62.9 in the second cycle achieving a score of 92 or Magnifying 29.1 points, and from the first cycle reaching a score of 71.5 cycles II achieving a score of 92 or an increase of 20.5 points or an increase in the score of Hindu religious learning outcomes, respectively by 8.6 points, 29.1 points, and 20.5 points.